'City as Home': Conducting walking interviews as biographical method with migrant men in Cork. Issue 1 (April 2023) - Fathi, Mastoureh
This paper builds on the growing interest in using walking interviews and visual methods to understand stories of place-making in migration. Walking offers a mobile way of being in the space that combines and connects our sense of self to objects, spaces and people who inhabit them. In this paper, I am using the recent approach in walking methods developed byO'Neill and Roberts (2020) called the Walking Interview as Biographical Method (WIBM hereafter) to discuss my experiences of conducting walking interviews with young male migrants in Cork, Ireland. The paper explores how 'city as home' is understood from a female researcher's perspective of or when doing research with male participants, and approaches WIBM from four perspectives: WIBM as temporal, WIBM as embodied, WIBM as spatial and WIBM's tacit mode. The paper's contribution is to detail the potential of WIBM's modes as a method of place-making in urban settings among migrant groups.